Gender and Development in the Middle East and North Africa : Women in the Public Sphere - World Bank (Washington, DC, 2013)
Gender inequality-the differential access to opportunity and security for women and girls-has become an important and visible issue for the economies of the Middle East and North Africa (MENA). Gender equality issues in MENA are usually approached from a social, anthropological, or political angle. But the costs of inequality are also borne at the economic level. This book seeks to advance the gender equality discussion in the region by framing the issues in terms of economic necessity. It analyzes the potential for women's greater economic contribution to the region's new development model, which is further discussed in three parallel books on trade, employment, and governance. It identifies key economic and sociopolitical impediments to women's increased labor force participation and empowerment, and it suggests a way forward in developing an agenda for change. MENA's achievements in many areas of women's well-being compare favorably with those of other regions. Indicators such as female education, fertility, and life expectancy show that MENA's progress in those areas in recent decades has been substantial. Where MENA falls considerably short is on indicators of women's economic participation and political empowerment (figure O.1). MENA's rate of female labor force participation is significantly lower than rates in the rest of the world, and it is lower than would be expected when considering the region's fertility rates, its educational levels, and the age structure of the female population.